O Modelo Randall-Sundrum sob mudança tipo Simpson-Visser - Lobo, Mauro Henrique Silva (2024)
This paper will address the Randall-Sundrum Type I and Type II models, both developed by the authors: Lisa Randall and Raman Sundrum. In type I, we will discuss a solution to the hierarchy problem: a discrepancy between the intensity of the gravitational field found on the TeV scale compared to that expected on the Planck scale (10^18 GeV). In type II, we will discuss in detail how gravity will behave and how the gravitational field we experience in our Universe emerges from this model. In order to observe how changes in the σ(y) function of the warp factor affect the structure of the system, we will submit these models to a Simpson-Visser type transformation of variables, and analyze how the new metric will behave.